Macroeconomic Factors as Determinants of Property Values in Indonesia - Rosyidatul Munawwaroh; Riyanto, Feri Dwi; Hasan, Irmayanti; Salis, Rohmatulloh (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of Regional Consumption Level (RCL), Gross Regional Domestic Product (GRDP), and Money Supply (MS) on property values in Indonesia, with inflation as a moderating variable. Using panel data from 33 provinces during 2020–2025, the study employs panel regression and Moderated Regression Analysis (MRA). The results indicate that RCL and MS have a positive and significant effect on property values, while GRDP has no significant effect. Furthermore, inflation is unable to moderate the relationships between RCL, GRDP, and MS and property values. These findings suggest that property values in Indonesia are primarily influenced by macroeconomic fundamentals rather than inflation dynamics. Keywords: property value, regional consumption rate, GDP, money supply, inflation, macroeconomics